Innovations in Engineering for Safety: Risk Control and Occupational Health in Deep-Sea Sampling with Modified Research Equipment - Nurlaela, Eli; Sudrajat, Danu; Nugraha, Erick; Nababan, Sakti Pandapotan; Choerudin, Hery; Rafith, Rafith; Saktianto, Nofendy Dwija; Gunawan Tampi, Estefanus; Derahmat, Mahardhika; Mantani, Sayuri (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
Occupational Health and Safety (OHS) is vital in high-risk environments, especially on research vessels conducting deep-sea sampling operations. The increased risk of accidents in maritime research requires an urgent focus on implementing specialized OHS systems. This study aims to analyze the application of OHS during deep-sea sediment sampling on the KM Madidihang 03 vessel. The research employs a descriptive design using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. Data were collected through direct observation during operations, utilizing modified Box Core and Gravity Core equipment for sediment collection. The hydraulic crane and tension meter were used to ensure the safe operation of these instruments. Data were analyzed to identify hazards, assess risks, and implement appropriate control measures. The results indicate that equipment failure, such as crane malfunction and cable breakage, poses the highest risk, necessitating regular equipment maintenance and safety training. The study recommends enhancing OHS procedures, including stricter supervision and crew training, to mitigate accidents and improve safety on research vessels. Future studies should focus on developing advanced safety protocols tailored to modified deep-sea research operations.